2012
DOI: 10.1537/ase.100929
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular phylogenetic characteristics of dwarf <i>Sus</i> specimens from the Noguni shell middens in the Ryukyu Islands

Abstract: We analyzed the morphological and molecular phylogenetic characteristics of Sus bone and tooth specimens excavated from the Noguni shell midden and the Noguni B shell midden (c. 7200-4400 uncal. BP), in Okinawa main island. They were compared with those of Sus remains from later sites on the Okinawa Islands (c. 4800-1400 uncal. BP) as well as modern Ryukyu wild boar (Sus scrofa riukiuanus). Based on the length and breadth of lower third molars, Sus specimens from the Noguni shell middens were distinctly smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The sequences of the mtDNA control region from 30 pigs were obtained from the National Center for Biotechnology Information (NCBI) database (GenBank) (Table 1): 11 indigenous pigs from China, 4 pigs from Taiwan, 1 pig from Korea, 3 Japanese wild boars ( Sus scrofa leucomystax ), 5 Ryukyu wild boars ( Sus scrofa riukiuanus ) and 6 domestic pigs from Europe. Furthermore, the haplotypes of the Agu pig identified in this study were compared with five ancient mtDNA haplotypes unearthed at archaeological sites (7200–1700 years before the present; BP) on Okinawa Islands [6,7] (NCBI GenBank; Table 2). The five Ancient haplotypes have been classified into East Asian domestic pigs by phylogenetic analysis [6,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the mtDNA control region from 30 pigs were obtained from the National Center for Biotechnology Information (NCBI) database (GenBank) (Table 1): 11 indigenous pigs from China, 4 pigs from Taiwan, 1 pig from Korea, 3 Japanese wild boars ( Sus scrofa leucomystax ), 5 Ryukyu wild boars ( Sus scrofa riukiuanus ) and 6 domestic pigs from Europe. Furthermore, the haplotypes of the Agu pig identified in this study were compared with five ancient mtDNA haplotypes unearthed at archaeological sites (7200–1700 years before the present; BP) on Okinawa Islands [6,7] (NCBI GenBank; Table 2). The five Ancient haplotypes have been classified into East Asian domestic pigs by phylogenetic analysis [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…Although the details of the origins of the Agu are not yet understood, It is generally believed that the ancestors of the Agu pig were introduced from the Asian continent in the latter half of the 14th century when the ancient Kingdom of Okinawa began to trade with China [4,5]. Nonetheless, recent studies on ancient mitochondrial DNA (mtDNA) from bones excavated at archaeological sites have suggested that the introduction of domestic pigs to Okinawa from the Asian continent dates back to prehistoric times [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, both Tokunoshima and Kakeroma populations exhibited a high percentage of convex bases in mandibles, commonly observed in domestic breeds (Anezaki, 2004). Since ancient times, transporting animals from one area to another is not a rare occurrence (e.g., Watanobe et al, 2002 ;Takahashi et al, 2012), and they may have been introduced from Okinawa to be kept and consumed. Genetic contamination of the indigenous population by introduced Sus is a serious concern today (Kurosawa, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Ryukyu wild boars show a large geographic variability in their size and also in their morphology. Morphological and genetic studies on different populations of Ryukyu wild boar have been published (Hayashida, 1960 ;Senba, 1964 ;Imaizumi, 1973 ;Hayashi, 1975 ;Kawashima et al, 1982 ;Hayashi et al, 1983 ;Kurosawa et al, 1986 ;Kurosawa and Tanaka, 1988 ;Endo et al, 1994Endo et al, , 1998aEndo et al, , b, 2000Endo et al, , 2002Watanobe et al, 1999 ;Takahashi et al, 2012). These studies demonstrated that the body size of Ryukyu wild boars is small compared to the Japanese wild boar (Sus scrofa leucomystax), the subspecies distributed in mainland Japan.…”
Section: Introductionmentioning
confidence: 99%
“…To verify these possibilities, it seems effective that genetic analyses that treat samples derived from both present and past periods, such as those by Nagata et al (2009) are needed. Furthermore, ancient DNA analyses of Sus scrofa bone that excavated from archaeological sites has been carried out in Japan Takahashi et al, 2012). Genetic information from these ancient DNA analyses is also useful for identification of native population of wild boar in each locality of Japan.…”
Section: ©2018 Reviews In Agriculturementioning
confidence: 99%